Determination of Moisture Sorption Isotherm of Crosslinked Millet Flour and Oxirane Using GAB and BET - M. S. Alamri; A. A. Mohamed; S. Hussain; M. A. Ibraheem; Akram A. Abdo Qasem (Journal of Chemistry)
Epoxy resin was prepared by crosslinking epoxidized oil and millet flour. The reaction was carried out at three different temperatures (25, 40, and 55°C) and zinc chloride levels (1, 2, and 3%). Moisture sorption isotherms were determined at 0.1 to 0.9 water activity (aw) using a gravimetric sorption analyzer (Q 2000). The sigmoidal shape (type II) of the resin isotherms exhibited lower equilibrium moisture content (EMC) at higher temperature. The experimental data were modeled using GAB (Guggenheim–Anderson–de Boer) and BET (Brunauer–Emmett–Teller). The EMC of the resin was significantly lower than that of the flour, which could be attributed to the decrease in the number of water-binding sites due to the creation of dense areas during crosslinking. The low root-mean-square error (RMSE) indicates that GAB and BET were suitable for predicting the water sorption isotherm for millet flour resin. The heat of sorption of the resin was large at low moisture content and increased at higher relative humidity. It is recommended that millet flour resin be used at relative humidity below 60%.